A new objective function for the assembly line balancing optimization in terms of workers’ global competence - CHOURABI, ZOUHOUR; BABAY, AMEL; KHEDHER, FAOUZI; CHEIKHROUHOU, MORCHED (Industria textilă (Bucharest, Romania : 1994), 2020)
This paper proposes an optimization model for the Assembly Line Balancing Problem (ALBP) in order to improve the work group choice in clothing industry. Traditionally, ALBP deals with several objectives like minimization of workstations number, minimization of cycle time, maximization of workload smoothness, and maximization of work relatedness…but neglect operators’ performance. As the worker competence is crucial to both product quality and productivity, an approach is proposed to balance production line through optimal operators’ assignment with the consideration of their skill levels. Based on two criteria, which are the Quality Index “QI” and the Activity “A”, each worker was evaluated in each executed operation. From these individual criteria, global indicators of the work group selected were proposed. Applying the Weighted Sum Model (WSM) a more general indicator which is the global Competence Index “CI g” was presented. Using simple linear regression model, the global competence was modelled. Thereafter, the model was validated and justified. The resulting performance indicator allowed predicting the global competence level, comparing different balancing proposals and making an optimal choice. So, a new objective function to maximize can be used in ALBP resolution in order to optimize the selected group capability.